The Santa Clause - Krumholtz, David; 1978-; Brandenberg, Larry; Gross, Mary; 1953-; Lloyd, Eric; 1948-; 1957-; Boyle, Peter; Crewson, Wendy; Reinhold, Judge; 1953-; et al. (Burbank, CA, 2002)
Scott is distressed to learn that his ex-wife and her husband have informed his son, Charlie, that there is no Santa Claus. While a sullen Charlie visits his dad on Christmas Eve, a noise on the roof brings them outside. It turns out that there is a Santa after all, and Scott has just accidentally killed him. Because of "the Santa clause, " Scott inherits the job of Santa. As the next year passes, Scott rapidly gains weight, grows a white beard and meets the elf Bernard. Charlies stepdad becomes concerned about Scotts and forces him to undergo a psychiatric evaluation.
Keywords: Drama; Fathers and sons; Santa Claus; Drama; Films for the hearing impaired; DVD-Video discs; Video recordings for the hearing impaired; Feature films; Christmas films; Comedy films